Validation of molecular markers for pod shattering tolerance in soybean [Glycine max (L.) Merrill]: VALIDATION OF MOLECULAR MARKERS FOR POD SHATTERING TOLERANCE IN SOYBEAN - D P MOHEKAR; D S THAKARE; M P DESHMUKH; S S DODAKE; V P CHIMOTE (Journal of Oilseeds Research, 2019)
Tagging of pod shattering/dehiscence tolerance trait in soybean (qPDH loci) with molecular markers was undertaken in a segregating population of cross cultivar Kalitur (shattering of 12.02% at field level; 77.71% on oven drying) x DS-9712 (shattering of 1.63% at field level; 10.94% on oven drying) by bulked segregant analysis (BSA). Pod shattering was partially dominant over the tolerance in the cross. Inhibitory epistasis of two major genes was evidenced from F2 ratio (13:3) (3.0-16.0% shattering field level and 5-85% on oven drying), with chi-square test indicating goodness of fit which was confirmed by test cross. Only two of the five shortlisted microsatellite markers from previous study viz., Satt674 and SRM1generated polymorphism between shattering tolerant and susceptible parents and their corresponding F2 bulks. Satt674 marker alleles were closely placed (223 bp vrs. 228 bp) hampering clear resolution and hence this primer was not used forfurther validation. SRM1 primer yielded distinct polymorphic markers (237bp vrs. 225 bp) between shattering-tolerant and susceptible parents and bulks. SRM1 marker was validated in 60 individual F2 plants which were contrasting for pod dehiscence trait. Forty-seven susceptible plants yielded either only 237 bp bands or were heterozygous (having both 237 bp and 225 bp bands), while 13 shattering tolerant F2 plants amplified only 225 bp marker. Hence, in future this SRM1-225bp marker linked to a major pod shattering tolerance loci qPDH1, could be utilized for screening the parental lines, segregating generations, breeding lines and varieties of soybean.